Engineering geological mapping: selected case studies in Malaysia - Mogana, S. N.; Komoo, I. (Journal of Nepal Geological Society, 2000)
Engineering geological maps are essential background data to the planning of land use, and design, construction, and maintenance of civil engineering works. They contain important information on ground conditions for the safe engineering construction. This paper provides three examples of the advantages of engineering geological mapping during the planning stage of the projects. The maps provided the preliminary information to engineers who were then able to make decisions regarding further investigation and feasibility of the projects. The paper further highlights the importance of executing a thorough engineering geological mapping before the commencement of a project.